“Me likey!” A new (old) argument structure or a partially fixed expression with the verb like? - Rodríguez-Abruñeiras, Paula (Círculo de Lingüística Aplicada a la Comunicación, 2022)
This paper explores the current use of the verb like in sequences such as “me likey”. This new use is practically limited to modern variant spellings (likey, likee, like-y and likie) and resembles the original (and now obsolete) impersonal structure of the verb in which the experiencer was encoded in the objective case and the verb was used invariably, among other aspects. However, rather than the re-emergence of an impersonal construction, the sequence “me likey” seems to be the result of a situation of language contact and it is in line with the informalisation of English as seen, for example, in the increasing tendency for objective pronouns to be used in subject position in a variety of constructions. In light of the evidence from the Corpus of Contemporary American English and the TV Corpus, we can conclude that the sequence is used in highly informal registers, and that it tends to appear in rather formulaic expressions, especially in two-word sequences.
Keywords: like/likey; argument structure; impersonal constructions; language contact